PENGARUH PESONAL SELLING DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN POLIS ASURANSI JIWA PT. ASURANSI JIWASAYA (PERSERO) CABANG PEKANBARU - Tamba, Ida Royani; ", Rizikna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The purpose of this research to find out how about the implementation promotion strategy (advertising, personal selling, public relation, sales promotion, and direct marketing) for achieve the room and to find out how the consumesâ interest about (liking, preference, and conviction)The population of this research is the consumers of Hotel Mutiara Merdeka Pekanbaru. The number of this samples are 98 people The search procedure of respondents performed by accidental sampling. Collecting research data form the primary data, using questionnaires as research instruments, data analysis used is by using multiple linear regression analysis with SPSS.From the results of data analysis includes test validity, reliability, and multiple linear regression, the implementation of personal selling in this study include the search for prospecting, targeting, communication, ellings and allocation. While the quality of services tangible, empathy, responsivennes, reliability and assurance. The results showed no significant effect between personal selling on purchasing decisions by the calculation of the t (5.506)> t table (1.985), then there is a significant influence between the quality of service on purchasing decisions by the calculation of the t (3.317)> t table (1.985 ) and is based on simultaneous test concluded that personal selling and service quality jointly influence the purchase decision.Keywords: personal selling, quality of service and purchasing decisions